2012
DOI: 10.3354/meps09662
|View full text |Cite
|
Sign up to set email alerts
|

Swimming patterns of larval Strongylocentrotus droebachiensis in turbulence in the laboratory

Abstract: We exposed 4-arm plutei of the sea urchin Strongylocentrotus droebachiensis to 2 levels of turbulent dissipation rates (ε: 9 × 10 −9 or 4 × 10 −7 W kg −1 ) in the laboratory, generated by using an oscillating metal grid. We compared direction of displacement and vertical velocities of larvae in turbulence with those of larvae in no flow and of passive particles in turbulence, for 2 different larval populations and over 2 trials. In turbulence, larval and passive particle movements were measured using particle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…Although some species of cyprids have been reported to be more abundant near the sea surface [28][29][30], we previously demonstrated that cyprids of all species recruited almost entirely to the bottom of moorings just outside the surf zone over 5 years on this coast [31]. Hence, cyprids may descend near the bottom as they enter the surf zone regardless of their depth preferences, before they reach the surf zone in response to increased turbulence from shoaling waves, as do other zooplankters in response to turbulence [12,13]. Benthic streaming also may deliver heavy zooplankters that passively sink to the bottom following mixing by large waves [27], whereas lighter zooplankton that do not swim downward would take longer to reach the bottom following mixing by small waves.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although some species of cyprids have been reported to be more abundant near the sea surface [28][29][30], we previously demonstrated that cyprids of all species recruited almost entirely to the bottom of moorings just outside the surf zone over 5 years on this coast [31]. Hence, cyprids may descend near the bottom as they enter the surf zone regardless of their depth preferences, before they reach the surf zone in response to increased turbulence from shoaling waves, as do other zooplankters in response to turbulence [12,13]. Benthic streaming also may deliver heavy zooplankters that passively sink to the bottom following mixing by large waves [27], whereas lighter zooplankton that do not swim downward would take longer to reach the bottom following mixing by small waves.…”
Section: Discussionmentioning
confidence: 99%
“…Virtual larvae were released hourly for 48 h and were initially distributed 410 m offshore at the DSZ site (602 larvae released) and 350 m offshore of the RSZ site (637 larvae released). Simulated larvae swam downward at 210 23 m s 21 until they encountered high turbulence (energy dissipation rate more than 10 25 m 2 s 23 ) in the surf zone, where their downward swimming increased to 210 22 m s 21 , based on the responses of larvae to turbulence in the laboratory [12,13]. We did not include rollers from breaking waves, which could increase onshore larval transport and wave reflection, which could limit onshore transport.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies revealed turbulence-induced downward movement can be seen in other intertidal invertebrates (Roy et al 2012;Fuchs et al 2013), so this behavior seems to be common in many intertidal larvae. In addition to vertical movement, horizontal swimming (which we ignored because we focused on the importance of vertical motions of weak swimmers) could also help for the crossshore migration by relatively strong swimmers such as fish and crab larvae.…”
Section: Discussionmentioning
confidence: 99%
“…By regulating their depth, larvae of some species recruit onshore in surface waters, whereas other species recruit onshore near the bottom in upwelling regimes (Morgan et al 2009a). Furthermore, larvae of various invertebrate taxa sink under turbulent conditions (Fuchs et al 2004(Fuchs et al , 2013Roy et al 2012). We hypothesize that depth preferences and sinking behavior help larvae to avoid strong offshore currents or enter the surf zone in streaming currents.…”
mentioning
confidence: 99%